Identification of antiviral secondary metabolites from sweet lemon grass, Cymbopogon nardus (L.) Rendle, inhibiting measles virus - Mardziah, binti Manas (2014)
An in vitro study was carried out to investigate the antiviral effects of sweet lemon grass (Cymbopogon nardus (L.) Rendle) on measles virus (MV). Crude extract of this plant were prepared using hexane and fractionation of this extract was done using column chromatography (CC). First CC produced a total of 20 combined fractions and further fractionation on selected fractions resulted in 77 combined subfractions. The toxicity of all fractions and subfractions towards Vero cells ranged from mildly toxic (50 μg/ml) to considerably non-toxic (600 μg/ml). In the antiviral test, majority of the fractions inhibited the production of MV-induced cytopathic effects (CPE) by more than 50%. Some of them were able to inhibit the CPE by more than 75%, which was similar to the activity showed by positive control, Ribavirin, which is 80%. Most of the subfractions conferred around 50% of protection to the cells, but majority of them had lower antiviral activity compared to their derived fractions.In an attempt to study the mode of antiviral action, pre-treatment and post-infection protocols were used. It was found that post-infection protocol was more effective among fractions, suggesting that the fractions may interfere with any of the steps in late stage of MV replication. However, the subfractions did not give any particular trend as to the most effective method of treatment. Active subfractions were then further purified using preparative thin layer chromatography (PTLC) and produced 11 isolated compounds. These compounds possess weak antiviral activity with majority of them inhibited less than 50% of virus CPE. Most of isolated compounds provided better protection to the cells in the pre-treatment protocol, suggesting that the potential sites of activity may include inhibition of virus binding and/or entry which can be mediated by a number of cellular receptors such as CD46 present on Vero cells. Meanwhile for the synergistic assay, the combination of Ribavirin with isolated compounds at lowest concentration (0.01 LC50) produced synergistic effect, either in one or both protocol. The clear synergistic tendencies displayed by these substances combination allows for the reduction of Ribavirin concentration, which minimizes toxicity and the probability of formation of resistance to this drug. This synergistic activity is probably connected to the different mechanisms of action of Ribavirin and isolated compound. Additional test, antiproliferation assay, showed that the isolated compounds possess weak activity towards human papillary ovarian adenocarcinoma (Caov-3) cancer cells as they were able to inhibit less than 50% of the cells growth at highest concentration tested. Result also showed that they were toxic to normal cells as their cytotoxic values on cancer cells (>400 μg/ml) were much higher than that of the normal cells (150 to 270 μg/ml) and the reference drug, Tamoxifen (150 μg/ml). The GCMS analysis revealed that majority of the active isolated compounds had more than one constituent that were accounted for their inhibitory activity. The constituents are made up of monoterpene, sesquiterpene and hydrocarbon that present commonly in the essential oil of C. nardus, such as methyl eugenol, citronellol and geraniol.